THEORETICAL SUBSTANTIATION OF INTERNATIONAL MULTIMODAL TRANSPORT INDICATORS AND IMPROVEMENT OF INTERNAL NORMS (ResearchJet Journal of Analysis and Inventions, 2021)
Recommendations have been developed to theoretically substantiate the indicators of international multi-modal transportation and to improve domestic standards.